P.147 Ruptured Intracranial Infectious Aneurysms: Single Canadian Center Experience. (November 2021) - Son, M; Kiwan, R; Mayich, M; Boulton, M; Pandey, S; Sharma, M
Abstract : Background: Ruptured Intracranial Infected Aneurysms (IIAs) are a relatively rare phenomenon, but they portend high mortality. To our knowledge, there are no Canadian studies on IIA with paucity of data on experiences as well. Our purpose is to share experience of a single Canadian tertiary centre in managing ruptured IIA and to conduct a systematic review. Methods: Retrospective case series review of adult patients with ruptured IIA treated at our institution. Secondly, we conducted a systematic review of literature on ruptured IIA between 2011-2021 inclusive. Results: At our institution, with a total 8 cases with ruptured IIA, 4 patients were treated endovascularly and 2 by surgical bypass. For the systematic review, we included 12 non-comparative studies with a total of 547 patients with IIA. Median percentage of ruptured IIA was at least 65.2%, cases that required intervention was 23.7% for surgical cases, and 50% for endovascular cases. The overall median percentage of complications was 5.3%. Conclusions: This study highlights a single Canadian tertiary centre experience in the management of IIA and compares it to the global trends of the last 10 years in a systematic review.